2023
DOI: 10.5217/ir.2021.00166
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and usefulness of transabdominal ultrasonography in immune-mediated colitis

Abstract: ry diseases; the latter are called "immune-related adverse events" (irAEs). 10 Among irAE-related studies, patients diagnosed with immune-mediated colitis (IMC) based on imaging data and abdominal symptoms accounted for 5% to 16% of those treated with anti-CTLA-4 antibodies and 1% to 2% of those treated with anti-programmed cell death receptor 1 (PD-1)/anti-PD-ligand 1 (PD-L1) antibodies. 11 IMC can occur at any time, i.e., in some cases, IMC develops a few days after initiating treatment, while in others, ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…51 Although cross-sectional imaging by computed tomography or magnetic resonance imaging has a limited role in diagnosing ICI-induced colitis, it may be useful in patients with severe symptoms (fever, severe pain) to rule out serious complications, such as perforation. 50 In a recent prospective study by Sakurai et al, 53 the ultrasonographic findings of ICI-induced colitis were determined along with the colonoscopic index. The authors indicated that these findings were primarily similar to those of ulcerative colitis and that ultrasonography could be useful for noninvasive monitoring of patients with ICI-induced colitis.…”
Section: Ici-induced Colitismentioning
confidence: 99%
“…51 Although cross-sectional imaging by computed tomography or magnetic resonance imaging has a limited role in diagnosing ICI-induced colitis, it may be useful in patients with severe symptoms (fever, severe pain) to rule out serious complications, such as perforation. 50 In a recent prospective study by Sakurai et al, 53 the ultrasonographic findings of ICI-induced colitis were determined along with the colonoscopic index. The authors indicated that these findings were primarily similar to those of ulcerative colitis and that ultrasonography could be useful for noninvasive monitoring of patients with ICI-induced colitis.…”
Section: Ici-induced Colitismentioning
confidence: 99%